Germ Cell Tumors in Children: A Retrospective Review of a 04-Year Single-Center Experience - Aftab, Kanwal; Ambreen, Fatima; Maqsood, Sidra; Yaqoob, Nausheen; Jamal, Saba (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Pediatric germ cell tumors (GCTs) are rare neoplasms that can be benign or malignant and occur in children and adolescents. They can arise from germ cells in the extragonadal or gonadal sites and have numerous histologic subtypes. The International Germ Cell Cancer Cooperative Group classification is used to guide treatment, with most children experiencing excellent overall survival (OS). Chemotherapy is historically recommended for all malignant GCTs. Nevertheless, surgery and observation alone may be sufficient for stage I gonadal GCTs. Using chemotherapy can lead to successful salvage of relapses..Objectives Our institute has conducted a study with the objective of evaluating a group of 97 patients diagnosed with GCTs, who received treatment within the past 4 years.Materials and Methods From January 2018 to April 2022, a total of 97 pediatric patients diagnosed with GCTs underwent surgical treatment at Indus Hospital & Health Network. The diagnosis was established by considering clinical features, tumor marker levels, imaging, and histology. Treatment was determined based on the risk stratification utilizing the United Kingdom Children's Cancer Study Group GC 2005–04 protocol. Patients classified as LR (low-risk) received chemotherapy only if a recurrence occurred after the initial surgery. On the other hand, IR (intermediate-risk) and HR (high-risk) patients received four and six cycles of JEB (chemotherapy regimen), respectively, followed by surgery. Recurrence was closely monitored through suspicion, tumor marker levels, or imaging. Patients experiencing a recurrence after JEB chemotherapy were treated with TIP (paclitaxel, ifosfamide, and cisplatin) chemotherapy and subsequently underwent surgery.Results In this retrospective study, a group of 97 patients diagnosed with GCTs was analyzed. The cohort included 59 gonadal tumors and 38 extragonadal tumors. The most common histopathological types observed were yolk sac tumor and dysgerminoma. Out of the patients, 33 (34%) were classified as HR, 35 (36.1%) as IR, and 29 (29.9%) as LR. Among the patients, 16 experienced recurrence, while the remaining 90 patients (92.8%) were alive at the time of the analysis. The study determined the 5-year event-free survival (EFS) rate as 83.5% and the OS rate as 92.8%. The presence of residual disease was found to be the only significant factor that influenced EFS.Conclusion To manage GCTs in children, a multidisciplinary approach involving surgeons, oncologists, and radiation therapists is required. Surgery and chemotherapy have improved outcomes for children with GCTs, but personalized treatment planning is crucial. With advancements in pediatric oncology care, the prognosis for children with GCT in Pakistan has improved, providing hope for better outcomes in the future.
Keywords: germ cell tumors (GCT); children; gonadal; yolk sac tumor; overall survival; event-free survival